Co4N/nitrogen-doped graphene a non-noble metal oxygen reduction electrocatalyst for alkaline fuel cells - Varga Tamás (APPLIED CATALYSIS B-ENVIRONMENTAL, 2018)
Abstract Cobalt-nitride (Co4N) nanoparticle-decorated nitrogen-doped graphene sheets were obtained via the nitrogen doping of a graphene-oxide precursor and simultaneous nitride formation. The non-precious metal catalyst formed in this one-step synthesis exhibits high electrocatalytic oxygen reduction activity and hence provides a promising alternative to conventional Pt/C alkaline fuel cell cathode catalysts. The reported composites were formed from the mixture of lyophilized graphene-oxide nanosheets and cobalt(II) acetate in ammonia atmosphere at 600 °C. The average Co4N particle size increased from 14 to 201 nm with the increase in cobalt content. The oxygen reduction activity of the new catalysts was comparable to that of non-noble metal systems described in the literature, and also to the widely-used carbon black supported platinum catalysts. The highest reduction current density under alkaline conditions was found to be as high as 4.1 mA cm−2 with the corresponding electron transfer number of 3.6. Moreover, the new system outperformed platinum-based composites in terms of methanol tolerance, thus eliminating one of the major drawbacks (besides high price and limited availability), of noble metal catalysts.